Penerapan Extreme Programming (XP) pada Sistem Informasi Pembayaran Asuransi Perbaikan Kendaraan di CV Tiara Persada Berbasis Web - Dini Hari Pertiwi; Halimah Evia Agustini; Hendra Effendi; Maria Veronica (Jurnal Informatika Global, 2022)
CV Tiara Persada is a company engaged in motor vehicle repair services, especially private cars or city cars, CV Tiara Persada also collaborates with several vehicle insurance companies to carry out vehicle repairs based on the insurance company's recommendations. The problem that often occurs at CV Tiara Persada in the process of repairing vehicles from insurance companies is that there is often a difference in payment between submitting a damage claim and working on damage because you have to submit multiple times and have to wait for an email approval from the insurance. With these problems, we need a web-based system that functions to carry out transactions and communication so that the payment process is not an obstacle. This system was built using the extreme programming method by carrying out several stages including Planning, Design, Coding, Testing and Software Increment. The purpose of building this system is to facilitate the process of managing insurance data, company spare parts data, repair data, insurance survey data, invoice reports and insurance customer reports. Then in this application there are 5 users, namely insurance, leadership, chief mechanic, cashier and customer service.Keywords: Vehicle Insurance, extreme programming (XP), Information Systems, Web Based.